Cross-Cultural Adaptation, Validity, and Reliability of the Turkish Version of the Cumberland Ankle Instability Tool for Athletes - Yazgan, E.A.; Karagözoğlu Coşkunsu, D.; Razak Özdinçler, A.R.; Coşkunsu, Dilber Karagözoğlu; Özdinçler, Arzu Razak (Human Kinetics Publ Inc, 2025)
CONTEXT: To cross-cultural translate the Cumberland Ankle Instability Tool (CAIT) to Turkish version (CAIT-T) and to evaluate the validity, reliability, and cutoff score of CAIT-T for Turkish athletic population. DESIGN: The English version of CAIT was translated to CAIT-T based on a guideline of cross-cultural adaptation. Fifty-two athletes with chronic ankle instability and 63 athletes without chronic ankle instability were included in the study. Construct validity was evaluated with correlations between the CAIT-T, Turkish version of Foot Ankle Ability Measure (FAAM-T), and Numeric Rating Scale. CAIT-T was completed twice by each participant at 7 to 10 days intervals to assess test-retest reliability based on the intraclass correlation coefficient, whereas Cronbach alpha evaluated internal consistency. Discriminative validity and content validity of the CAIT-T also evaluated. RESULTS: In construct validity, strong positive correlation was found between CAIT-T and Numeric Rating Scale perceived ankle instability (rho = -.771, P < .001), as well as moderate negative correlations with FAAM-T-activities of daily living and FAAM-T-sports (rho = -.448, P < .001 and rho = -0.541, P < .001, respectively). The CAIT-T demonstrated strong test-retest reliability (intraclass correlation coefficient score of .98) with a good internal consistency (Cronbach α: .85). Receiver operating characteristic curve showed a cutoff score of 26.5 (Youden index: 0.78, sensitivity: 0.57, specificity: 0.90.5). No ceiling or floor effects were observed. CONCLUSIONS: CAIT-T is a valid and reliable questionnaire for the assessment of chronic ankle instability in the Turkish athletic population. This record is sourced from MEDLINE/PubMed, a database of the U.S. National Library of Medicine
Keywords: CAIT; Chronic Ankle Instability; Self-Report Questionnaire